Representasi Pesan Moral dalam Film Dokumenter ”Ngawitan Ngariksa Jagat” - Yoga Anggara; Haryadi Mujianto; Ismira Febrina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
“Ngawitan Ngariksa Jagat” is a documentary genre film offering that shows the lives of the Sundanese Wiwitan harmonious community. This film is an orientation documentary genre in discussing the Sundanese Wiwitan perspective in general society and the perspective of the wider community. This research uses a descriptive qualitative approach with Roland Barthes' semiotic analysis method, which involves examining signs in videos at three levels: connotation (figurative meaning), denotation (actual meaning), and myth (history). Data is collected through documentation from relevant sources such as journals, books, films and websites. Primary data comes from observations of the film